COMPARISON BETWEEN ORGANIC MATTER CONTENT OF MAIN SOIL ORDERS IN KURDISTAN REGION USING TWO DIFFERENT METHODS. - & Esmail, Khoshnaw (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted to compare between two methods of soil organic matter determination for main soil orders in Kurdistan region/Iraq, for this purpose forty-five soil samples were taken then the organic matter was determined using chemical (Walkley-Black (wet) method and loss-on-ignition method (dry) combustion method. The results indicated the significant correlation (r = 0.88**) between the studied methods It means there is good adjustment to convert organic matter by loss-on-ignition method (dry) to Walkley-Black (wet) method organic matter by this linear equation (organic matter by loss-on-ignition =1.651* Walkley-Black method organic matter +2.1877) this equation can be used to convert organic matter by two methods for Mollisols(M), Vertisols(V) and Aridisols(A) in Hawler(H), Sulaimani(S) and Duhok(D) governorates, this equation is very important and economic to determine and convert dry method to wet method, the amount of organic matter for M, V, A was recorded the highest value (49.5, 24.8, 20 gkg-1) respectively for Mollisols, Vertisols, and Aridisols at Hawler (H), Sulaimani (S), and Duhok(D) respectively for (DM5, SV4, DA1) in Duhok Mollisols, Sulaimani Vertisols and Duhok Aridisol respectively for walk- black (wet) method, the highest value for dry method organic matter in Mollisols, Vertisols, Aridisols was recorded (97.6, 77.9, 50.3 g kg-1) for soil orders (MD3, VD4, AD4) respectively.